"Getting Out of That Siloed Mentality Early": Interprofessional Learning in a Longitudinal Placement for Early Medical Students. (January 2020) - Rivera, Josette; O'Brien, Bridget; Wamsley, Maria
Abstract : Purpose: Although descriptions of interprofessional education often focus on interactions among students from multiple professions, embedding students from 1 profession in clinical settings may also provide rich opportunities for interprofessional learning (IPL). This study examines affordances and barriers to medical students' interactions with and opportunities to learn from health care professionals while learning health systems science in clinical workplaces. Method: In May 2017, 14 first-year medical students at the University of California, San Francisco participated in a semistructured interview about IPL experiences during a 17-month, weekly half-day clinical microsystem placement focused on systems improvement (SI) projects and clinical skills. Communities of practice and workplace learning frameworks informed the interview guide. The authors analyzed interview transcripts using conventional qualitative content analysis. Results: The authors found much variation among the 14 students' interprofessional interactions and experiences in 12 placement sites (7 outpatient, 4 inpatient, 1 emergency department). Factors influencing the depth of interprofessional interactions included the nature of the SI project, clinical workflow, student and staff schedules, workplace culture, and faculty coach facilitation of interprofessional interactions. Although all students endorsed the value of learning about and from diverse health care professionals, they were reluctant to engage with, or "burden, " them. Conclusions: There are significant IPL opportunities for early medical students in longitudinal placements focused on SI and clinical skills. Formal curricular activities, SI projects conducive to interprofessional interactions, and faculty development can enhance the quality of workplace-based IPL. Abstract : Supplemental Digital Content is available in the text.